Factors That Influence Utilization Toddler Posyandu in the Puskesmas Working Area Medan Durian Shop Year 2023 - Siregar, Julaiha (Jurnal EduHealth, 2023)
Posyandu is one of the government programs that plays a very important role in monitoring and developing the health of mothers and children under five. Through this program we can find out the health and nutritional status of children who are good as well as poor nutrition of children under five which can increase cases of maternal and child deaths. The aim of This research aims to find out the factors that influence the use of posyandu for toddlers in the working area of the durian shop public health center. This research is a type of quantitative research with a survey method, cross sectional in nature with a sample size of 86 mothers of toddlers. The research instrument was a questionnaire and data analysis was carried out using the chi square test at a real level of α=0.05. The linear regression test stated that the most dominant variable had an influence on cadre services on the utilization of Posyandu services (p=0.000) on a prevalence ratio (RP) of 21.10; 95%CI (5.42-82.18). It is recommended that posyandu cadres be expected to implement the 5 table system in implementing the posyandu and be more aggressive in conducting outreach regarding the benefits, goals and growth and development of children, so that all members of the community can make maximum use of the posyandu program. The linear regression test stated that the most dominant variable had an influence on cadre services on the utilization of Posyandu services (p=0.000) on a prevalence ratio (RP) of 21.10; 95%CI (5.42-82.18). It is recommended that posyandu cadres be expected to implement the 5 table system in implementing the posyandu and be more aggressive in conducting outreach regarding the benefits, goals and growth and development of children, so that all members of the community can make maximum use of the posyandu program.